STAC3 variants cause a congenital myopathy with distinctive dysmorphic features and malignant hyperthermia susceptibility. Issue 12 (11th October 2018) - Zaharieva, Irina T.; Sarkozy, Anna; Munot, Pinki; Manzur, Adnan; O'Grady, Gina; Rendu, John; Malfatti, Eduardo; Amthor, Helge; Servais, Laurent; Urtizberea, J. Andoni; Neto, Osorio Abath; Zanoteli, Edmar; et al.
Abstract: SH3 and cysteine‐rich domain‐containing protein 3 (STAC3) is an essential component of the skeletal muscle excitation–contraction coupling (ECC) machinery, though its role and function are not yet completely understood. Here, we report 18 patients carrying a homozygous p.(Trp284Ser) STAC3 variant in addition to a patient compound heterozygous for the p.(Trp284Ser) and a novel splice site change (c.997‐1G > T). Clinical severity ranged from prenatal onset with severe features at birth, to a milder and slowly progressive congenital myopathy phenotype. A malignant hyperthermia (MH)‐like reaction had occurred in several patients. The functional analysis demonstrated impaired ECC. In particular, KCl‐induced membrane depolarization resulted in significantly reduced sarcoplasmic reticulum Ca 2+ release. Co‐immunoprecipitation of STAC3 with CaV 1.1 in patients and control muscle samples showed that the protein interaction between STAC3 and CaV 1.1 was not significantly affected by the STAC3 variants. This study demonstrates that STAC3 gene analysis should be included in the diagnostic work up of patients of any ethnicity presenting with congenital myopathy, in particular if a history of MH‐like episodes is reported. While the precise pathomechanism remains to be elucidated, our functional characterization of STAC3 variants revealed that defective ECC is not a result of CaV 1.1 sarcolemma mislocalization or impaired STAC3‐CaV 1.1 interaction. Abstract : In this study, we describe the largest cohort of patients with STAC3 ‐related congenital myopathy. Seventeen patients carried the homozygous p.Trp284Ser STAC3 variant, previously described as causative for Native American myopathy (NAM), and one patient was compound heterozygous for the NAM variant and a novel splice site variant. The functional analysis demonstrated impaired excitation‐contraction coupling with significantly reduced Ca 2+ release in response to KCl‐induced membrane depolarisation while the protein interaction between STAC3 and CaV1.1 was not significantly affected by the STAC3 variants.